Developing Countermeasures of Integrating Entrepreneurship Education with Professional Education in Colleges and Universities Using Data Mining - LiLi Deng (Journal of Electrical and Computer Engineering)
The purpose is to promote the integrated development of innovation and entrepreneurship education (IEE) and professional education (PE) in colleges and universities (CAUs) more accurately and efficiently. Data mining (DM) technology is introduced to study IEE + PE in CAUs. At present, although the state strongly supports the IEE + PE, the integration progress is still slow, and IEE and PE are still completely independent of each other. Therefore, it is urgent to combine IEE with PE organically. Accordingly, based on DM technology, this work analyzes the current situation and existing problems of IEE + PE and puts forward suggestions and corresponding countermeasures for the future development of IEE + PE. The results show the following: (1) College students have high expectations of cultivating their innovation and entrepreneurship ability. (2) The internal and external influencing factors of IEE must be merged. (3) The implementation methods of IEE should be diversified. (4) The current resource allocation of IEE is unreasonable. Based on the above analysis, the existing problems are studied in detail and the corresponding countermeasures are put forward. Meanwhile, DM technology provides a theoretical data basis, making the research results more authentic and reliable and providing reference suggestions for IEE + PE.